Traditional Chinese Medicine Injections Combined With Antihypertensive Drugs for Hypertensive Nephropathy: A Network Meta-Analysis - Chen, Zhe; Peng, Yingying; Yang, Fengwen; Qiang, Xiaoyu; Chen, Yong; Chen, Yongjie; Cao, Lujia; Liu, Chunxiang; Zhang, Junhua (Frontiers in Pharmacology, 2021)
Background: Hypertension, a risk factor for cardiovascular events, is often associated with chronic kidney disease. This is called hypertensive nephropathy (HN), which negatively affects physical fitness and body mass, leading to economic burden. Traditional Chinese medicine injections (TCMIs) are common traditional Chinese-patent medicine preparations in China. There was a lack of evidence to prove which TCMIs combine with ADs (TCMIs+ADs) may be a therapeutic option for HN. Thus, we systematically reviewed the efficacy and safety of various TCMIs + ADs in patients with HN. Methods: We conducted a comprehensive search of PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform, and VIP information resource integration service platform databases for relevant Chinese- and English-language randomized controlled trials (RCTs) published from database inception until May 2021. Literature screening, data extraction, and quality assessment was performed by two reviewers independently but using the same criteria. We performed the effect modeling to analyze the data for all outcomes and ranked each intervention using the P-score. Furthermore, sensitivity analysis, meta-regression, and funnel plots were used to test the stability, heterogeneity, and publication bias, respectively. Results: We included 69 RCTs with 6373 patients and including six TCMIs + ADs. Network analysis indicated that the ginkgo leaf extract and dipyridamole combined with ADs (GLED + ADs) was the most efficacious in terms of 24-h urinary protein excretion [mean difference (MD) = −0.70, 95% confidence interval (CI): −0.82 to −0.58; P-score = 1] and systolic blood pressure (MD = −12.95, 95% CI: −21.03 to −4.88; P-score = 0.88), whereas the salvianolate combined with ADs (SA + ADs) showed the highest effectiveness for diastolic blood pressure (MD = −6.88, 95% CI: −10.55 to −3.21; P-score = 0.9). Based on the combined P-score of network meta-analysis results (88% and 85.26%) and sensitivity analysis results (72% and 71.54%), the biplots showed that the GLED + ADs was the most efficacious intervention in all TCMIs + ADs for primary outcomes, followed by the SA + ADs and sodium tanshinone IIA sulfonate combined with ADs (STS + ADs). There was no significant difference in terms of safety between TCMIs + ADs and ADs alone. Conclusion: Of all the TCMIs + ADs, GLED + ADs, SA + ADs, and STS + ADs may demonstrate a higher efficacy than ADs alone for HN. Weighing with the potential benefits and limitations in methodology, potential heterogeneity and outcomes, we should use various TCMIs with caution in clinical practice. Nevertheless, additional high-quality RCTs are warranted and future research should focus on the clinical value of core outcomes to confirm the effectiveness and safety of TCMIs for HN. Systematic Review Registration: clinicaltrials.gov, identifier CRD42020205358